2008
DOI: 10.1177/1065912908317033
|View full text |Cite
|
Sign up to set email alerts
|

Community Context, Personal Contact, and Support for an Anti—Gay Rights Referendum

Abstract: Using data from an unusual survey, we gauge factors influencing support for a state anti-gay rights referendum. After controlling for other powerful predictors of attitudes, we find personal contact (especially relevant and voluntary contact) has an important impact on public support, although community context does not. These findings support an integrated notion of interactions with "out" groups, grounded in social categorization theory, that sees community context and interpersonal contact as concentric cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(50 citation statements)
references
References 39 publications
2
47
0
1
Order By: Relevance
“…Second, previous studies have found that favorable attitudes toward same-sex households and education are positively related (Herek and Capitanio 1996; Barth et al 2009). For instance, Barth et al (2009) found a 22 percentage point difference in support for an anti-gay rights referendum between those in the lowest educational category (no high school diploma) and those in the highest educational category (postgraduate education).…”
Section: Literature Reviewmentioning
confidence: 95%
See 1 more Smart Citation
“…Second, previous studies have found that favorable attitudes toward same-sex households and education are positively related (Herek and Capitanio 1996; Barth et al 2009). For instance, Barth et al (2009) found a 22 percentage point difference in support for an anti-gay rights referendum between those in the lowest educational category (no high school diploma) and those in the highest educational category (postgraduate education).…”
Section: Literature Reviewmentioning
confidence: 95%
“…For instance, Barth et al (2009) found a 22 percentage point difference in support for an anti-gay rights referendum between those in the lowest educational category (no high school diploma) and those in the highest educational category (postgraduate education). Higher levels of education in the place may be accompanied by more favorable attitudes toward same-sex households, promoting lower segregation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Other aspects of embeddedness could have produced different results. Information on contextual factors such as living in LGB neighborhoods, visiting LGB establishments, or befriending other activists could have enhanced the role of immersion factors (Barth et al 2009;Lombardi 1999;Waldner 2001;Worthington et al 2005). Other studies suggest that knowingan LGB professor can increase LGB activism as well (Johnson and Lollar 2002).…”
Section: Discussionmentioning
confidence: 91%
“…Across the literature, gender, age, religious affiliation, religious intensity, education, income, marital status, ethnicity, and contact with gay people have all been suggested as significant sources of variation in attitudes on gay rights issues. In most studies, males, older respondents, Protestants, Catholics, those with greater church attendance, those with less education, lower-income respondents, African Americans, Latinos, married respondents, those from rural areas, Southerners, and those with limited contact with gays and lesbians all demonstrated lower support for same-sex marriage and were more likely to vote for bans (Barth, et al 2009;Baunach 2012;Becker 2012aBecker , 2012bBecker and Scheufele 2009;Brewer 2008;Brumbaugh, et al 2008;Burnett and Salka 2009;Dyck and Pearson-Merkowitz 2012;Egan and Sherrill, 2009;Fleischmann and Moyer 2009;Gaines and Garand 2010;Lewis and Gossett 2008;McKenzie and Rouse 2013;McVeigh and Diaz 2009;Olson et al 2006;Salka and Burnett 2012;Sherkat et al 2010;Sherkat et al 2011). Several of these studies report inconsistent results for some variables including gender, age, income, ethnicity, and marital status.…”
Section: Factors Influencing Opinion On Same-sex Marriagementioning
confidence: 99%
“…As of 2012, Republicans and conservatives generally opposed same-sex marriage by large margins (60 to 80% opposition); Democrats and liberals supported same-sex marriage by equally large margins (see, for example, Barth et al 2009;Becker and Scheufele 2009;Becker 2012a).…”
Section: Factors Influencing Opinion On Same-sex Marriagementioning
confidence: 99%